Entre prácticas, instituciones y discursos: trabajadores infantiles en la ciudad de México (1920-1934) - Sosenski, Susana (El Colegio de México, A.C., 2010)
This paper reveals the social action of children in Mexico City once the armed period of the Revolution was over. it analyzes the different  forms of economic participation among Mexican children and shows the various public attitudes and policies towards them. Moreover, the essay presents a quantitative and qualitative approach to urban child labor and examines the different governmental attempts to institutionalize it in schools and reformatories. The children’s role as social actors is foregrounded by studying children and teenagers as individuals who participate in their own lives, in their families’ lives, in the economic life of the country, and in the construction of the Mexican State.